RELASI EKSPRESI MATERIAL TERHADAP PREFERENSI PENGUNJUNG DI ARAH KOPI SUKAJADI BANDUNG - Farhan, Muhammad; Guawan, Yenny (Jurnal Riset Arsitektur, 2025)
Abstract - Cafes have become popular places for many people to relax, work, or simply enjoy a cup of coffee. Visitors often have a tendency to choose spaces that suit their preferences and needs. One of the factors that influence visitors' decisions in choosing space in a café is the purpose of their visit or the atmosphere created in it which can affect visitor preferences. Arah Kopi Sukajadi Bandung has an architectural design that uses various materials in various spaces. This unique feature prompted research to investigate how the expression of these materials affects the perception and overall experience of visitors at the Arah Kopi Sukajadi Bandung café. The study also considered the tactile aspects of the materials used in the designated space. With the variety of spatial atmospheres created, uploading researchers to understand how material expression relates to visitor preferences in choosing a sitting area to use. It was concluded that basically the material that is very influential in creating a comfortable atmosphere in a café consists of natural materials, such as wood, rocks, to the surface of grass and water. This surface tends to be chosen because it has a perception that reminds humans of the natural environment and creates a calm, cool, and cool perception. In addition, material expression has a relationship with visitor preferences in choosing a sitting area to use during their activities in the Sukajadi Coffee Direction because material expression is one of the important factors in creating a comfortable atmosphere in a space in a café and is something that humans are able to feel directly which is influenced by visual and tactile sensory stimuli to create good perception. Keywords: material expression, perception, sensory system, atmosphere of space, café